Report of Meeting Researches in Didactics of Mathematics and Computer Sciences: January 26-28, 2018 Hajdúszoboszló, Hungary (Teaching Mathematics and Computer Science, 2018)
The meeting Researches in Didactics of Mathematics and Computer Sciences was held in Hajdúszoboszló, Hungary from the 26th to the 28th of January, 2018. It was organized by the Doctoral School of Mathematical and Computational Sciences of University of Debrecen.The 61 participants – including 47 lectures and 17 PhD students – came from 8 countries, 21 cities and represented 37 institutions of higher and secondary education.